The Effects of Dexmedetomidine on Perioperative Neurocognitive Outcomes After Noncardiac Surgery: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 1 (1st March 2022) - Singh, Amara; Broad, Jeremy; Brenna, Connor T. A.; Kaustov, Lilia; Choi, Stephen
Abstract : Objective: The purpose of this review is to examine the effect of dexmedetomidine on delayed neurocognitive recovery (dNCR; cognitive dysfunction ≥1 week postoperative) after major noncardiac surgery. Background: Dexmedetomidine (DEX) effectively reduces delirium in the intensive care unit and reportedly attenuates cognitive decline following major noncardiac surgery. Ascertaining the true effect on postoperative cognition is difficult because studies are limited by suboptimal selection of cognitive assessment tools, timing of testing, and criteria for defining significant cognitive decline Methods: Prospective randomized trials comparing perioperative DEX to placebo for major noncardiac surgery assessing cognitive function ≥1 week postoperative were included. Pediatric, nonhuman, and non-English trials, and those where executive function was not assessed were excluded. Data were abstracted by 3 reviewers independently and in parallel according to PRISMA guidelines. The a priori binary primary outcome is dNCR defined as cognitive function declining by the minimal clinically important difference or accepted alternate measure (eg, Reliable Change Index ≥1.96). Bias was assessed with the Cochrane Collaboration tool. Data were pooled using a random effects model. Results: Among 287 citations identified, 26 (9%) met criteria for full-text retrieval. Eleven randomized trials (1233 participants) were included for qualitative analysis, and 7 trials (616 participants) were included for meta-analysis of dNCR. Dexmedetomidine did not reduce the incidence of dNCR significantly (OR 0.57, 95% CI 0.30–1.10, P = 0.09) compared with placebo. There was no difference in the incidence of delirium (OR 0.94, 95% CI 0.55–1.63, P = 0.83) and a higher incidence of hemodynamic instability (OR 2.11, 95% CI 1.22–3.65, P = 0.008). Conclusions: Dexmedetomidine does not reduce dNCR 1 week after major noncardiac surgery. This meta-analysis does not yet support the use of perioperative DEX to improve short term cognitive outcomes at this time; trials underway may yet change this conclusion while larger trials are needed to refine the point estimate of effect and examine long-term cognitive outcomes. Abstract : Mini-Abstract: In this systematic review, the incidence of delayed neurocognitive recovery was not reduced with intraoperative dexmedetomidine compared to placebo or alternate sedation. An effect on postoperative delirium was not observed; however, there was an increased incidence of hemodynamic instability associated with dexmedetomidine. Supplemental Digital Content is available in the text.